Diclofenac Mouthwash as a potential therapy for reducing pain and discomfort in chemo‐radiotherapy–induced oral mucositis. (10th March 2020) - Brennan, Peter A.; Lewthwaite, Rowena; Sakthithasan, Poornima; McGuigan, Sharon; Donnelly, Oliver; Alam, Peyman; Gomez, Ricardo S.; Fedele, Stefano
Abstract: Aims: Oral and/or oropharyngeal acute mucositis during and after chemo‐radiotherapy (chemo‐RT) for head and neck squamous cell carcinoma (HNSCC) can be extremely painful, sometimes requiring nasogastric feeding to enable adequate nutrition. The MASCC/ISOO evidence‐based guidelines recommend benzydamine mouthwash for mucositis prevention in RT (recently updated to include chemo‐RT), and a Cochrane systematic review found other agents to be effective in prophylaxis. Diclofenac mouthwash is licensed for painful oral mucosal inflammatory conditions but to our knowledge has not been assessed in chemo‐RT–associated oral mucositis. Method: A clinical observation and service evaluation study in 10 patients undergoing chemo‐RT for HNSCC to assess the potential value of diclofenac mouthwash (0.74 mg/mL) in reducing symptoms. Patients used 20ml of mouthwash up to 4 times a day starting in week 3 (of a 6‐week course of treatment), recording pain and discomfort scores using a visual analogue scale on days 0, 1, 7 and 14 (until the end of week 4). As per our current clinical practice, oral mucositis was not clinically scored as an outcome. Statistical analysis was performed using a one‐way ANOVA. Results: Using diclofenac mouthwash, 9/10 patients experienced pain score reduction from day 0 (mean score 6.75 ± SD 1.83) to day 2 (5.05 ± SD 1.62) and day 14 (4.09 ± SD 1.96). Conclusions: Diclofenac mouthwash may be beneficial for managing chemo‐RT–induced oral mucositis. While a prospective randomised clinical trial is needed, it can be prescribed for this condition within its current licence.